The Evolution of Securities Market Organisation - Jan Allen Kregel (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1994)
An analysis of Walras' and Marshall's explanation of competitive price notes that both model actually existing, but different, forms of trading in stock markets, a call auction and a continous auction respectively. Although Walras uses market organisation to ensure complete information, under simultaneous trading his analysis joints Marshall who assumes the existence of "perfectly informed dealers". The paper build on the problems of market regulation in condition of simultaneous and continous tradeing to aasess the evolution of the New York market from call to the continous trading and the institution of singl capacity trading with fixed commissions on the London market.
Keywords: 330